Cell Seeding on UV‐C‐Treated 3D Polymeric Templates Allows for Cost‐Effective Production of Small‐Caliber Tissue‐Engineered Blood Vessels. Issue 1 (21st December 2018) - Galbraith, Todd; Roy, Vincent; Bourget, Jean‐Michel; Tsutsumi, Tamao; Picard‐Deland, Maxime; Morin, Jean‐François; Gauvin, Robert; Ismail, Ashraf A.; Auger, François A.; Gros‐Louis, François
Abstract : There is a strong clinical need to develop small‐caliber tissue‐engineered blood vessels for arterial bypass surgeries. Such substitutes can be engineered using the self‐assembly approach in which cells produce their own extracellular matrix (ECM), creating a robust vessel without exogenous material. However, this approach is currently limited to the production of flat sheets that need to be further rolled into the final desired tubular shape. In this study, human fibroblasts and smooth muscle cells were seeded directly on UV‐C‐treated cylindrical polyethylene terephthalate glycol‐modified (PETG) mandrels of 4.8 mm diameter. UV‐C treatment induced surface modification, confirmed by Fourier‐transform infrared spectroscopy (FTIR) analysis, was necessary to ensure proper cellular attachment and optimized ECM secretion/assembly. This novel approach generated solid tubular conduits with high level of cohesion between concentric cellular layers and enhanced cell‐driven circumferential alignment that can be manipulated after 21 days of culture. This simple and cost‐effective mandrel‐seeded approach also allowed for endothelialization of the construct and the production of perfusable trilayered tissue‐engineered blood vessels with a closed lumen. This study lays the foundation for a broad field of possible applications enabling custom‐made reconstructed tissues of specialized shapes using a surface treated 3D structure as a template for tissue engineering. Abstract : Human skin and muscle cells are seeded directly on UV‐C‐treated small caliber mandrels. UV‐C treatment induced surface modification is necessary to ensure proper cellular attachment. This rapid and cost‐effective approach generates solid tubular conduits with high level of cohesion between concentric cellular layers and improved mechanical properties. This study lays the foundation for a broad field of possible applications enabling custom‐made reconstructed tissues of specialized shapes using a surface treated structure as a template for tissue engineering.